Engineering Nano Filtration-Based Clean Water Technology to Improve Coastal Public Health - Raodatul Putri (ARMADA : Jurnal Penelitian Multidisiplin, 2025)
The clean water crisis is still a major problem in Indonesia's coastal regions, especially in areas with high levels of salinity and complex biological pollution. This study aims to examine the application of nanofiltration technology based on activated carbon zeolite composite material to improve the quality of water suitable for consumption for coastal communities. The research method used an experimental approach by testing the effectiveness of the filtration system against physical parameters (turbidity, color, conductivity), chemical (pH, nitrates, ammonia), and microbiological (E. coli and coliform). The test results showed that the use of a 50–80 nm porous nano-zeolite layer was able to reduce turbidity by up to 93%, TDS by up to 85%, and suppress the number of coliform bacteria by up to 99.5%. The cost analysis also shows economic efficiency because the basic materials used are relatively cheap and easy to obtain in the local area. These findings confirm that nanofiltration engineering is not only a technological solution, but also an ecological and social approach to guarantee sustainable access to clean water in coastal areas.